THE IMPLEMENTATION OF THE NURSING PROCESS IN A PERSON WITH MENTAL HEALTH PROBLEMS: A CASE REPORT - Žigić, Ana; Pavlović Jugović, Katarina; Lazić, Slavica; Jovanović, Vesna R. (HEALTH CARE, 2026)
Introduction/Aim: The Nursing Process (NP) represents a fundamental, systematic, and individualized method of work in nursing that enables a holistic approach to the patient. Its application is of particular importance in psychiatric care, where the needs of users are complex and require continuous monitoring of subjective and objective indicators of mental state. The aim of this paper is to demonstrate the application of the NP in a person with a chronic mental disorder through a case report. Case report: The research was conducted at the Home for Mentally Ill Persons "1. oktobar" in Stari Lec. The subject is a 61-year-old male patient with a medical diagnosis of F20.0 (paranoid schizophrenia). The patient has been institutionalized since 2013, and the clinical presentation is characterized by auditory hallucinations, rapid thought flow (tachypsychia), elevated mood (hyperthymia), and increased volitional activity (hyperbulia) without the realization of plans. Additionally, sleep disturbance (insomnia) and strained family relationships with the father were identified. By applying the NP, seven nursing diagnoses were identified. The care plan included 15 independent and 6 interdependent nursing interventions. Key nursing measures included: establishing a therapeutic relationship and trust; continuous monitoring and control of hallucinations; implementing a hygienic-dietary regimen to regulate sleep; guiding the patient during logorrheic speech; providing support in maintaining social contacts with his sons. The evaluation determined partial achievement of goals in terms of behavioral stabilization and better cooperation in self-care activities. Conclusion: The case report confirms that the NP allows for a comprehensive assessment of the patient’s needs and a clear definition of the nursing role within a multidisciplinary team. It is essential to implement the NP into mandatory nursing documentation at the national level to ensure the quality, continuity, and legal security in the treatment and care of persons with mental health disorders.